People with intellectual disabilities and labour market inclusion: What role for EU labour law?. Issue 1 (March 2020) - Bell, Mark
People with intellectual disabilities occupy a peripheral position in the labour market. They have low rates of participation in employment and this often takes the form of sheltered employment in settings segregated from persons without disabilities. Although their working lives have received limited attention in legal scholarship, this article argues that law can play a positive role in fostering greater inclusion. Taking into account the UN Convention on the Rights of Persons with Disabilities, this article analyses EU legislation and case law in order to identify how these apply to those working in sheltered employment and how they may assist in tackling barriers to participating in the open labour market. While EU labour law already contains measures that have the potential to improve the position of people with intellectual disabilities, the article identifies scope for enhancing the effectiveness of these instruments.